Analysis of optical fiber differential protection based on relay protection. Issue 2 (March 2021) - Fan, Hongshen
Abstract: In order to prevent grade-jumping tripping in coal mine distribution network, based on the analysis of the causes of grade-jumping tripping, several schemes to prevent grade-jumping tripping are compared and analyzed, and the fiber current differential protection scheme is suitable for application in working environment. In this paper, the main technology of optical differential protection, in the process of 6 KV power distribution system reform is how to apply this situation are introduced in detail, at the same time, a detailed description of the relative performance for the optical fiber differential protection, a comprehensive discussion of PCS-9613D fiber protection setting calculation and adjustment method, look forward to applying the experience of the use of short transmission optical differential protection.